Cooperative Institutional Research Program (CIRP) (United States): Freshman Survey, 1968 ([Verlag nicht ermittelbar], 2002)
The principal purposes of this national longitudinal study of the higher education system in the United States are to describe the characteristics of new college freshmen and to explore the effects of college on students. For each wave of this survey, students complete a questionnaire during freshman orientation or registration containing some 200 items covering information on academic skills and preparation, high school activities and experiences, educational and career plans, majors and careers, student values, financing college, and a variety of demographic questions such as sex, age, parental education and occupation, household income, race, religious preference, and state of birth. Specific questions asked of respondents in the 1968 survey included average grade in secondary school, how many colleges they had applied to for admission, accomplishments during their high school years, highest academic degree they intended to obtain, concerns about financing their education, if they were a twin, source of financing for the first year of school, academic standards and individual ranking at their high schools, size of locality in which they lived when growing up, and what they hoped to accomplish in college. Respondents were also asked to list their probable career occupation, first, second, and least appealing major field of study, and activities they engaged in during their previous year in school. Also elicited were respondents' opinions on the importance of various individuals and events in their decision to enroll in college, assessments of achieving certain goals during their college years, and general attitudes about faculty and other students.